PENGARUH ADVOKASI DAN FUNGSI KELUARGA TERHADAP KEBERHASILAN PROGRAM KAMPUNG KELUARGA BERENCANA DI DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KABUPATEN KARAWANG - Zulkifli Rangkuti; Juhro Juhro (Aliansi : Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine the effect of Advocacy and Family Function on the Success of the KB Village Program. The sampling technique used total sampling (n = 73), and the data analysis technique used Correlation and Regression with SPSS version 22. The results showed that Advocacy had a positive and significant effect on the success of the KB Village Program (t count = 2.854, p 0.06). Family function has a positive and significant effect on the success of the KB Village Program (t count = 2.791, p 0.38). Family advocacy and functions simultaneously had a positive and significant effect on the success of the KB Village Program (F arithmetic = 4.063, p 0.21). Contribution of Advocacy and Family Function to the Success of the KB Village Program is shown by the Adjusted R Square value of 0.604 or (60.4%). The remaining 39.6% is influenced by other variables. The implication of this research is that there must be a Karawang regency Population and Family Planning Office policy in increasing the success of the KB Village Kampung Program. To improve the success of the KB Village Program through the advancement of the Advocacy and monitoring of the Employees' Family Functions so that the Success of the KB Village Program is achieved.